Load Balancing in Software Defined Network - Kumari, P; Thakur, D (International Journal of Computer Sciences and Engineering, 2025)
Legacy heterogeneous network paradigm have reached the extremity where its competence to accustom to dynamic situation has become a hindrance. These traditional network platforms are very complicated to manage due to various challenges like interoperability, upgrade which require protocols and management techniques hard-coded into the underlying network platform. Software Defined Network is an emerging network architecture which allows automation of infrastructure configuration enabling the network operators to adapt their network to meet the real time application requirements. Now-a-days with the frequent and rapid inflation of number of clients associated with the network, it is very important to distribute the incoming request equally among all the servers. So by taking advantage of the overall view of the network by the controller, various load balancing strategies can be used to distribute the request in order to increase the overall performance of the system. Every load balancing technique has some pros and cons. This paper gives the comprehensive critical survey on various load balancing strategies used in SDN technology.